96.6k views
0 votes
Rewrite the function f(x)=-3(x+3)^2-13
in the form f(x)=ax^2+bx+c

2 Answers

6 votes

Answer:

-3x^2-18x-40

Explanation:

-3(x+3)^2-13

-3(x^2+6x+9)-13

-3x^2-18x-27-13

-3x^2-18x-40

User Bao Haojun
by
5.2k points
2 votes

Answer:

-3x^2-18x-40

Explanation:

(x+3)^2: x^2+6x+9

= -3(x^2+6x+9)-13

Expand:

-3(x^2+6x+9): -3x^2-18x-27

= -3x^2-18x-27-13

Final Answer: -3x^2-18x-40

Rewrite the function f(x)=-3(x+3)^2-13 in the form f(x)=ax^2+bx+c-example-1
User Walty Yeung
by
4.5k points